More than a Rumor Spreads in Parkinson's Disease - Prymaczok, Natalia C.; Riek, Roland; Gerez, Juan (Frontiers in Human Neuroscience, 2016)
As Parkinson's disease progresses, a massive loss of dopaminergic neurons is accompanied by accumulation of alpha-Synuclein (αSyn) neuronal inclusions called Lewy bodies and Lewy neurites. Inclusions first appear in olfactory bulb and enteric neurons then in ascendant neuroanatomical interconnected areas, and finally, in late stages of the disease, Lewy bodies are observed in a substantia nigra pars compacta with clear signs of neuronal loss. It is believed that the spreading of Lewy bodies through the nervous system is a consequence of the cell-to-cell propagation of αSyn, that can occur via sequential steps of secretion and uptake. Certain pathological forms of transmitted αSyn are able to seed endogenous counterparts in healthy recipient cells, thus promoting the self-sustained cycle of inclusion formation, amplification and spreading, that ultimately underlies disease progression. Here we review the cell-to-cell propagation of αSyn focusing on its role in the progression of Parkinson’s disease.